The importance of non-motor symptoms in the approach to Parkinson's Disease (Research, Society and Development, 2024)
Introduction: Parkinson's disease is a neurodegenerative condition which, in addition to the classic motor symptoms, presents various non-motor symptoms, such as sleep disorders, autonomic dysfunctions and neuropsychiatric alterations. These symptoms can precede motor symptoms and have a major impact on patients' quality of life, but they are often underdiagnosed. Objective: The aim of this study was to review contemporary and multidisciplinary approaches to non-motor symptoms in Parkinson's disease, highlighting the main points and scientific gaps. Materials and Methods: This is a narrative review of the literature on the non-motor symptoms of Parkinson's disease. The PICO strategy was used to develop the guiding question. In addition, the descriptors “Parkinson's Disease”; “Complications”; “Propaedeutics” were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: The studies show that the non-motor symptoms of Parkinson's disease present a varied spectrum of manifestations, ranging from sleep disorders to those related to the sensory system. Conclusion: The non-motor symptoms of Parkinson's disease play a central role in the progression of the disease and the impact on patients' quality of life. These symptoms result from neurodegeneration in various areas of the central and peripheral nervous system, highlighting the complexity of the disease. Thus, the recognition and effective management of non-motor symptoms are fundamental to improving prognosis.